689 Lactose Hydrogen Breath Test (Lhbt) in Children: Is it a Useful Tool?. (October 2012) - Upatissa, KM; Rodrigues, BF; Patel, H; Mahadevan-Bava, S
Abstract : Children with lactose malabsorption can present with chronic diarrhoea, increased flatulence, abdominal pain or constipation. The simple solution is a trial of Lactose free diet (LFD). Aim: and method: Our aim is to assess the usefulness of LHBT for objective measure of LI and appropriate dietary advice. We retrospectively reviewed 36 children with symptoms of Lactose Intolerance (LI), who underwent LHBT attending the paediatric gastroenterology clinic at RHH from 2009–2011. Results: 36 children (20M:16F) (34 Caucasian) aged 2–17 years were identified. All baseline tests and Coeliac screen were negative. The presenting symptoms: diarrhoea (12), flatulence (14), abdominal pain (10) IBS (2) and constipation (12). 12/36(33%) were positive (8/12 hydrogen load suggested LI and 4/12 small bowel bacterial growth) LHBT. 5/8 with positive LI, showed marked improvement on LFD. Although 24/36 were negative LHBT, 5/24 started trial of LFD with 3/5 success. Conclusion: LHBT is a simple non invasive and cost effective test that is useful in diagnosing LI in children. It gives objective evidence to parents to commence lactose free diet, thereby avoiding unnecessary omission of milk and dairy-products (19/36 potential cases in our study) that can have detrimental effects on calcium and vitamin D intake in children.